Beekeeping development opportunity for Serbian Danube - Nada Mijajlović; Slavica Arsic (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Beekeeping in the Serbian economy is one of the underdeveloped sector. Modern agriculture today can not be imagined without a developed and modern beekeeping as a part of agriculture and the national economy that is subject to economic laws that operate in the market and is inextricably linked to all the developments in the domestic and global economics. The importance of this activity is potentiated in this paper. The paper analyzed the production of honey, the total number of hives and honey production per hive in Central Serbia, Vojvodina and Serbian Danube region. The aim of this paper is to highlight the importance of beekeeping as an economic sector that has significant potential for sustainable development within the Serbian Danube region. The presented data related to beekeeping in statistical databases and literature data related to beekeeping.
Keywords: 330; beekeeping; honey production; sustainable development; Danube